Kepuasan Konsumen Sandal Swallow dengan Metode Statistik Deskriptif - Muhammad Azmii Sajid; Anisa Fadhila Mahsun; Diah Permata Hadainingrum (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2022)
This study aims to know how the quality and service of Swallow slip has a degree of customer satisfaction. The study was conducted ata total of 43 participants with 19 working participants, 24 of whom were 16 - year - old students or students Years and swallow slippers in the last six months. Data collection Is carried out using a likert scale method spread out.  Data analysis from this study uses descriptive statistic study that aims to know analysis to know consumer satisfaction swallow. The study used a measure of the lyert scale with four points. From religious testing, we identify the cronbach alpha score by 0875, and from validity tests, we use different power tests with no aitem with a differential test score of 0.3. The descriptive statistical analysis test was obtained that the service aspect of the total value 4, the average service satisfaction aspect of 3.5, the quality aspect of 3.6, the brand aspect of 3.6, and the price aspect of 3.5. With the average acquisition of every aspect as noted, it could be argued that the consumer was satisfied with swallow slippers.